Ecuador : Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Ecuador. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Ecuador's Request for Purchase Under the Rapid Financing Instrument (RFI). The Ecuadoran authorities are requesting financial assistance under the IMF's RFI to address the urgent balance of payments (BOP) needs associated with emergency and reconstruction efforts. Given the urgency of their request, they are not currently in a position to implement a full-fledged upper-credit-tranche program, and they believe they can make suitable adjustments to manage their medium-term BOP challenges. Given the nature of the emergency, the IMF staff supports the authorities' request for a purchase under the RFI.